Whole genome sequencing, comparative genomics and virulence factors analyses of Meyerozyma guilliermondii strain soexpression system - Zainudin, Robiatul Azilah (2021)
Meyerozyma guilliermondii strain SO isolated from spoiled orange has been developed as a free-inducer expression system and attains a positive impact in industrial recombinant proteins production. The comprehension on genomic features is necessitated to cater its competency to perform as an expression host. Furthermore, it may enhance the yield of production at lower cost in the absence of an inducer. Therefore, the complete genome data of M. guilliermondii strain SO representing the host system from the perspective of genome arrangement, polymorphic variants, the composition of genes and the association in metabolic pathway is prerequisite in genomic comparative and toxicity analyses. Thus, the genome data were generated from Illumina Hiseq 4000 sequencing platform and assembled into 51 scaffolds successfully accumulated into 10.63 Mbp. These enclosed 5,335 CDS genes and 5,349 protein sequences with 43.72% GC content. About 99.29% of it were annotated to public databases. These data were employed to conduct a comparison of M. guilliermondii intraspecies strains which comprises of SO, ATCC 6260, YLG18 and RP-YS-11. The study discovered 99.18% genes similarity among these strains and subsequently embarking high accuracy analysis. Besides, the evaluation of established yeast expression systems, Komagataella pastoris and Saccharomyces cerevisiae with our inhouse strain SO and the reference strain of M. guilliermondii were carried out comparatively to identify the consensus domain or subdomain that putatively responsible to perform as an expression host. A non-expression yeast species, Candida albicans was included in the investigation to structure normalization. This interspecies study revealed 666 homologous genes with 55 consensus regions of genome identified exclusively in M. guilliermondii and both expression hosts. Hence, the connectivity enzymes that played pivotal roles during carbon metabolism particularly on the utilization of methane was accessed. The study recognised an absence of alcohol oxidase (AOX) enzyme in strain SO which contributed to the factor of methanol-independency. This eventually highlighted the strength of M. guilliermondii strain SO to perform as a forthcoming freeinducer alternative host for recombinant protein expression. Additionally, the selected potential virulence factors in M. guilliermondii strain SO were determined from systemlevel insights. The algorithm of Hidden Markov Model detected in silico indication of proteases (SAP), phospholipases (PLC and PLD) and hemolysin (MAM3) motifs in the genome which possessed 85% similarity to C. albicans, a pathogenic yeast that caused candidiasis and triggering safety concerns. Hence, the investigation of apportioning virulence factors in strain SO to predict SAP, PLC, PLD and MAM3 were executed and identified the resemblance of C. albicans with the expect value 2.4e-107, 9.5e-200, 0.0e+00 and 1.2e-258, respectively. Accordingly, these significant genes possibly play roles in pathogenicity. The topology of phylogenetic analysis constructed strain SO and C. albicans branches from the same node and clustered together as a clade to signify molecular relatedness and congeneric among these species. Nevertheless, in vitro analysis in quantifying the level of expression need to be investigated from the assay to quantify the enzymatic activity which may and may not activate strain SO as an opportunistic pathogenic yeast, subsequently, certifying the toxicity status of M. guilliermondii strain SO.